2001
DOI: 10.1002/srin.200100120
|View full text |Cite
|
Sign up to set email alerts
|

A study of the dissolution of Al2O3, MgO and MgAl2O4 particles in a CaO‐Al2O3‐SiO2 slag

Abstract: The dissolution behaviour of alumina, MgO and MgAl2O4 particles in a 36%CaO‐21%Al2O3‐42%SiO2 (mass contents in %) slag has been studied using a confocal scanning laser microscope in the temperature range of 1470 ‐ 1550 °C. The double hot thermocouple technique and metallographic examination was also used to characterize the reaction product between the particles and the slag. The total dissolution times for MgO and MgAl2O4 particles decreased with increased temperature and were almost identical (approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 4 publications
1
63
0
Order By: Relevance
“…3,[8][9][10]13 This model assumes first order kinetics. Full details of the derivation and the applicability of this model can be found in Levinspiel.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10]13 This model assumes first order kinetics. Full details of the derivation and the applicability of this model can be found in Levinspiel.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years this has become a well accepted technique for studying inclusion behaviour, 2,9,12,13) capturing dissolution times and rates. A full description of the technique and the microscope has been described previously [9][10][11] with only the key details listed here.…”
Section: Confocal Scanning Laser Microscopementioning
confidence: 99%
“…Sridhar and co-workers [9,10] used confocal scanning laser microscopy to directly observe the dissolution of small MgO particles in calcium silica aluminate [9] and calcium aluminate [10] slags at temperatures ranging from 1450 °C to 1600°C. Convection effects were ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In these two studies, they reported conflicting rate controlling mechanisms for the MgO dissolution process. In the calcium silica aluminate [9] slag, it was concluded that boundary layer diffusion may be rate controlling, whereas in the calcium aluminate [10] slag, it was found that chemical reaction is rate limiting. Sridhar et al [9,10] make no comment on the different rate controlling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation